AB0091 Mathematical modeling of interleukin-6 signaling inhibition: Comparative efficiency of different intervention strategies. (23rd January 2014) - Young, D.; Maisonpierre, P.; Shaw, S.; Chan, J.; Kretsos, K.
Abstract : Background: A cascade of binding events between IL-6, IL-6R, and gp130 leads to formation of IL-6 signaling complexes in inflammatory conditions. 1 Tocilizumab (TCZ), an anti-IL-6R antibody (Ab), inhibits IL-6 signaling by preventing IL-6+IL-6R dimerization (axis 1 intervention). 2 Axis 1 intervention can also be achieved with anti-IL-6 Abs. Subsequent assembly steps present alternative strategies for IL-6 signal inhibition, including IL-6-targeted agents that prevent trimer formation (IL-6+IL-6R+gp130; axis 2 intervention) or the formation of the (IL-6+IL-6R+gp130)2 signaling hexamer (axis 3 intervention). Objectives: To investigate the potential impact of a number of prototypical therapeutic strategies for inhibiting formation of the IL-6 signaling complex, using a mathematical modeling system. Methods: We developed a dynamic, mathematical model of IL-6 signaling within a target compartment, with initial steady state IL-6, soluble (s) IL-6R, and sgp130 concentrations. The model encompassed IL-6 interaction with membrane-bound IL-6R ( cis ) or with both membrane-bound and sIL-6R ( cis and trans signaling), including the impact of inhibiting membrane-bound and sgp130 by different targeted strategies. The validity of the model was confirmed by comparison to published PK/PD data for TCZ. 3 Four prototypical intervention strategies were modeled: anti-IL-6R, axis 1; anti-IL-6, axis 1; anti-IL-6, axis 2; and anti-IL-6, axis 3. Simulations compared the sensitivity of drug responses to parameter variations at multiple clinically relevant IL-6, sIL-6R, and sgp130 concentration scenarios. All simulated parameters for interactions and responses were based on a one-compartment linear PK model. Results: Anti-IL-6 axis 3 intervention was predicted to be the most efficient inhibitor of combined cis + trans IL-6 signaling. This advantage held true both when IL-6 concentration was limiting, and under conditions of equimolar IL-6 and IL-6R. 4 The advantage of anti-IL-6 axis 3 intervention over anti-IL-6R or anti-IL-6 approaches to axis 1 intervention was robust to changes in single parameters, and was lost only in large excess of IL-6 over IL-6R or when multiple conditions coincided, such as a combination of: excess IL-6; inefficient Ab binding to membrane-bound targets; increased IL-6 turnover or slower IL-6R turnover; slow IL-6+IL-6R dimerization kinetics; and low Ab dissociation constant. Conclusions: Anti-IL-6 intervention at axis 3 may be more efficient at inhibiting IL-6 signaling than axis 1 intervention with an anti-IL-6R Ab, in either serum- or synovial-like conditions. Multiple factors simulating sensitivity of drug responses were required to challenge the advantage of axis 3 intervention. References: Boulanger MJ. Science 2003. Mihara M. Int Immunopharmacol 2005. Frey N. ACR 2007, Abst #259. Desgeorges A. J Rheumatol 1997. Disclosure of Interest: None Declared